A randomized Phase I vaginal safety study of three concentrations of C31G vs. Extra Strength Gynol II - Mauck, Christine K.; Weiner, Debra H.; Creinin, Mitchell D.; Barnhart, Kurt T.; Callahan, Marianne M.; Bax, Richard (Contraception (Stoneham), 2004)
C31G is an antimicrobial and spermicidal agent that contains two surface-active compounds, cetyl betaine and myristamine oxide. It is being developed as a vaginal microbicide and contraceptive. Three C31G concentrations (0.5%, 1.0% and 1.7%) were tested and compared with Extra Strength Gynol II®, a marketed spermicide containing 3% nonoxynol-9 (N-9), in a randomized, double-blinded, Phase I, dose-escalation study to assess genital irritation (by subject report, visual examination at pelvic examination and colposcopy), plasma and vaginal lavage levels of C31G, product leakage, systemic safety and acceptability. Women were randomized to use 3.5 mL of one of the three C31G products or the N-9 gel at night for 7 days then twice daily for another 7 days. Pelvic and colposcopic evaluations were performed after 7 and 14 days of product use. The percent of women experiencing irritation in the 0.5% and 1.0% C31G groups in the study were similar to each other and were lower than the percent experiencing irritation in the 1.7% and N-9 groups, which were also similar to each other. Differences were statistically significant between 1.0% C31G vs. N-9 at 7 days and between 0.5% C31G and 1.0% C31G vs. N-9 at 14 days. There was no significant difference between groups in leakage or acceptability. No C31G was detected in the plasma of any volunteer. These results suggest that 0.5% and 1.0% C31G are less irritating to the female genital tract than 1.7% C31G or Extra Strength Gynol II.